Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1158/0008-5472.can-08-1510
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A Causes FOXO3a- and Bim-Dependent Apoptosis and Inhibits Growth of Human Breast Cancer Cells In vivo

Abstract: Withaferin A (WA) is derived from the medicinal plant Withania somnifera, which has been safely used for centuries in Indian Ayurvedic medicine for treatment of different ailments. We now show, for the first time, that WA exhibits significant activity against human breast cancer cells in culture and in vivo. The WA treatment decreased viability of MCF-7 (estrogen-responsive) and MDA-MB-231 (estrogenindependent) human breast cancer cells in a concentrationdependent manner. The WA-mediated suppression of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
276
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 241 publications
(295 citation statements)
references
References 44 publications
19
276
0
Order By: Relevance
“…Tumor growth inhibition at this dose is consistent with a previous report showing a role of FOXO3A and Bim in the regulation of WFA-mediated apoptosis. 27 As the maximum dose of WFA (4 mg/kg) had minimal toxicity to normal tissue (Fig. 5), we suspect that greater WFA concentrations are safe with potentially greater antimetastatic and cytotoxic efficacy.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Tumor growth inhibition at this dose is consistent with a previous report showing a role of FOXO3A and Bim in the regulation of WFA-mediated apoptosis. 27 As the maximum dose of WFA (4 mg/kg) had minimal toxicity to normal tissue (Fig. 5), we suspect that greater WFA concentrations are safe with potentially greater antimetastatic and cytotoxic efficacy.…”
Section: Discussionmentioning
confidence: 86%
“…1a), consistent with previous reports. 27,28 In almost all cases, concentrations less than 500 nM had a negligible effect on proliferation. The apoptotic activity of WFA was assessed using cleaved PARP in MDA-MB 231 breast cancer cells and H1299 lung cancer cell lines.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…WA was dissolved in vehicle (10% DMSO, 40% cremophor:ethanol (3:1), and 50% PBS). 48 Tumor size and body weight were measured every 2 d from d 21 after implantation. The tumor volume was calculated by the formula: volume (mm 3 ) D (length £ width 2 )/2.…”
Section: Xenograft Experimentsmentioning
confidence: 99%
“…Several studies have been reported for its anti-tumor effects, including the inhibitory activities of tumor cell growth, angiogenesis and metastasis (Stan et al, 2008a;Mohan et al, 2004). Recently, a variety of biological roles of Wit A have been reported; induction of apoptosis by ROS generation (Malik et al, 2007;Lee et al, 2009), anti-proliferative effect of Wit A by G2/ M phase cell cycle arrest (Stan et al, 2008b), inhibition of cell adhesion molecules by inactivation of Akt and NF-jB (Oh and Kwon, 2009), and inhibition of cell migration/invasion through down-regulation of signal transducer and activator of transcription 3 (STAT3) activation in human breast cancer cells (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%